Transcranial Doppler scanning and the assessment of stroke risk in children with haemoglobin sickle cell disease. Issue 2 (9th October 2007) - Deane, Colin R; Goss, David; O'Driscoll, Sandra; Mellor, Sarah; Pohl, Keith R E; Dick, Moira C; Height, Sue E; Rees, David C
Abstract : Objective: : To assess the role of transcranial Doppler (TCD) scanning in assessing the risk of stroke in children with haemoglobin SC (HbSC) disease. TCD scanning has an established role in primary stroke prevention in sickle cell anaemia but its value in HbSC is unknown. Design: : A retrospective audit of routinely performed TCD scans and routinely collected clinical data. Setting: : A paediatric sickle cell clinic in a teaching hospital in south London, UK. Patients: : 46 children with HbSC disease who have undergone routinely performed TCD scans and steady-state blood tests. Main outcome measures: The time-averaged mean of the maximum velocity (TAMMV) in the middle cerebral artery circulation correlated with clinical and laboratory data. Results: The mean TAMMV was 94 cm/s, with a 98 th centile of 128 cm/s. This is significantly less than the published ranges for HbSS, with a mean reading of 129 cm/s. One child had a stroke at the age of 5 years, when her TAMMV was measured at 146 cm/s. Conclusions: Further studies are needed to assess stroke risk in HbSC disease, but we suggest that TCD measurements are potentially useful in this condition, and that readings greater than 128 cm/s are abnormally high and warrant further investigation.